Gender Differences in Professional Career Dynamics: New Evidence from a Global Law Firm - Ina Ganguli; Ricardo Hausmann; Martina Viarengo (Center for Economic Studies and ifo Institute (CESifo), 2020)
We examine gender gaps in career dynamics in the legal sector using rich panel data from one of the largest global law firms in the world. The law firm studied is representative of multinational law firms and operates in 23 countries. The sample includes countries at different stages of development. We document the cross-country variation in gender gaps and how these gaps have changed over time. We show that while there is gender parity at the entry level in most countries by the end of the period examined, there are persistent raw gender gaps at the top of the organization across all countries. We observe significant heterogeneity among countries in terms of gender gaps in promotions and wages, but the gaps that exist appear to be declining over the period studied. We also observe that women are more likely to report exiting the firm for family and work-life balance reasons, while men report leaving for career advancement. Finally, we show that various measures of national institutions and culture appear to play a role in the differential labor-market outcomes of men and women.
Keywords: I26; J16; J62; M51; Z10; 330; gender gaps; human capital; job mobility; promotion; culture; legal sector